THE EFFECT OF SHARIA AUDIT ON THE LEVEL OF PUBLIC TRUST IN THE NATIONAL ZAKAT AMIL TULUNGAGUNG - Siti Zulaekah Zulaekah; Triya Oftafiana; Mei Azizatur Rohmah (State Islamic Institute (IAIN) Tulungagung, 2022)
A sharia audit is a procedure that entails a systematic review of a sharia financial institution's whole operation for conformity with sharia rules. Internal audits, external audits, and any other activities requiring adherence to sharia principles are examples of these activities. Internal and external auditors can both do Sharia audits. The general public's trust is crucial to the efficacy of zakat management. In part, a sharia audit can be used to maintain and ensure the integrity of zakat management organizations in their implementation of sharia principles. The goal of this study was to use a descriptive quantitative research technique as well as a literature review from relevant sources, including earlier studies. The findings suggest that implementing a good and legal sharia audit in zakat institutions will have a significant impact on the level of public trust. Sharia-compliant auditing is an important part of restoring public trust in zakat institutions.